2014
DOI: 10.1007/s00784-014-1193-6
|View full text |Cite
|
Sign up to set email alerts
|

Six-month results following treatment of aggressive periodontitis with antimicrobial photodynamic therapy or amoxicillin and metronidazole

Abstract: In patients with AP, the two times application of aPDT in conjunction with nonsurgical periodontal therapy cannot be considered an alternative to the systemic use of amoxicillin and metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
107
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(123 citation statements)
references
References 29 publications
4
107
2
8
Order By: Relevance
“…55,56 The results have shown that both treatment protocols resulted in statistically significant improvements in PD reduction, gain of CAL and improvement in BOP compared to baseline. The systemic use of amoxicillin and metronidazole yielded however, at both 3 and 6 months, statistically significantly higher reductions in mean PD compared with the treatment using PDT.…”
Section: Use Of Pdt As An Alternative To Systemic or Local Antibioticsmentioning
confidence: 96%
See 2 more Smart Citations
“…55,56 The results have shown that both treatment protocols resulted in statistically significant improvements in PD reduction, gain of CAL and improvement in BOP compared to baseline. The systemic use of amoxicillin and metronidazole yielded however, at both 3 and 6 months, statistically significantly higher reductions in mean PD compared with the treatment using PDT.…”
Section: Use Of Pdt As An Alternative To Systemic or Local Antibioticsmentioning
confidence: 96%
“…The systemic use of amoxicillin and metronidazole yielded however, at both 3 and 6 months, statistically significantly higher reductions in mean PD compared with the treatment using PDT. 55,56 The most important clinical finding was the change in the total number of pockets ≥ 7 mm following both treatment protocols. In the PDT group, the total number of pockets ≥ 7 mm was reduced from 137 to 45 with the corresponding values of 141 and 3 in the amoxicillin and metronidazole group.…”
Section: Use Of Pdt As An Alternative To Systemic or Local Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma, as três concentrações do azul de toluidina e azul de metileno utilizadas foram 0,05 mg/ml (BERAKDAR et al, 2012;BALATA et al, 2013;PINHEIRO et al, 2010) ,0,1 mg/ml (AL-ZAHRANI et al, 2009;GE et al, 2011;NORO FILHO et al, 2012;THEODORO et al, 2012;BASSIR et al, 2013;FRANCO et al, 2014;MONGARDINI;DI TANNA;PILLONI, 2014) e 10 mg/ml (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;CAPPUYNS et al, 2012;GIANNOPOULOU et al, 2012;NOVAES et al, 2012;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;ARWEILER et al, 2014;BETSY et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;MOREIRA et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;ALWAELI;KHATEEB;AL-SADI, 2015;QUEIROZ et al, 2015). Apesar dos resultados do teste de concentração dos corantes, onde a concentração de 10mg/ml foi a única efetiva para o metileno e a de 5 e 10mg/ml foram as bactericidas para o toluidina, optamos por testar novamente as três concentrações mais comum na literatura acima citada.…”
Section: Discussionunclassified
“…Esse valor apresentou excelente efeito bactericida na presença de luz (ambas potências de laser e LED), quanto na ausência. Além do mais, é uma concentração de corante bastante utilizada em estudos clínicos (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008, CHONDROS et al, 2009, DE OLIVEIRA et al, 2009, LULIC et al, 2009, POLANSKY et al, 2009, SIGUSCH et al, 2010, CAPPUYNS et al, 2012, GIANNOPOULOU et al, 2012, NOVAES et al, 2012, CAMPOS et al, 2013, LUCHESI et al, 2013, ARWEILER et al, 2014, BETSY et al, 2014, KOLBE et al, 2014, MACEDO et al, 2014, MOREIRA et al, 2014, PETELIN et al, 2014, QUEIROZ et al, 2014, ALWAELI, KHATEEB, AL-SADI, 2015, QUEIROZ et al, 2015. Parece que a concentração alta do corante foi fator único para os resultados obtidos, não sendo necessário o uso da luz.…”
Section: Discussionunclassified